In Silico Genomic Study Of Phage Specific To Pseudomonas Aerigunosa Usm Ar2 - Zawawi, Nurul Ashiqin Mohamad (2018)
Advancement in cloning and sequencing technologies are producing a massive collection of bacteriophage or phage genomes. The complete genome sequencing and annotation of phage genome constitute important information in the discovery of highly diverse phage population. To better understand the biology of phage, in silico genomic analysis would allow the identification of viral genes and proteins. In this study, Pseudomonas phage SM1 genome was completely sequenced and composed of 93 191 base pairs in length, with G+C content of 55.2 %. Genome analysis of the double stranded DNA revealed 129 open reading frames (ORFs) present in the full genome. All of the ORFs were arranged on the positive strand except for one ORF. Based on several software analysis, 60 ORFs show no significant homology to the known proteins deposited in the databases and were considered as unique to this phage. Meanwhile, another 18 ORFs encode for known functional proteins and 51 ORFs encode for hypothetical proteins. Genome alignment of Pseudomonas phage SM1 against Pseudomonas phage complete genome sequences that were deposited in NCBI (National Center For Biotechnological Information) showed lack off similarities. Thus, suggesting Pseudomonas phage SM1 as a potential newly discovered Pseudomonas phage. The verification of the assembled and annotated results was performed by cloning ORF 1, encoding capsid containing scaffold protein in the E.coli system. The detection of homogenous particles resembling capsid-like morphology of Pseudomonas phage SM1 under transmission electron microscope (TEM) gave assurance that the recombinant capsid containing scaffold proteins was successfully expressed. Further peptide sequencing of purified capsid containing scaffold protein result confirmed the identity of the recombinant protein. Hence, the bioinformatics analyses of the genome sequence and annotation were verified for Pseudomonas phage SM1.